2003
DOI: 10.1152/jn.00875.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypodynamia-Hypokinesia on the Muscle Spindle Discharges of Rat Soleus Muscle

Abstract: Falempin. Effects of hypodynamia-hypokinesia on the muscle spindle discharges of rat soleus muscle. J Neurophysiol 89: 3000 -3007, 2003; 10.1152/jn.00875.2002. The aim of this study was to determine whether Ia and II fiber discharges of soleus muscle spindles were modified after a 14-day period of hypodynamia (absence of weight bearing) and hypokinesia (reduction of motor activity). Fifty-one and 38 afferent fibers were studied, respectively, in control and hypodynamia-hypokinesia (HH) groups. Under deep anes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…An over extended ankle at take off, but more flexed in the main part of the step cycle was also reported in adult suspended rats [28,42]. The ankle extension of suspended rats can be related to changes of paw pressure and muscles spindle stimulation [28,42]. This involves therefore a different mechanism than the one we observed on centrifuged mice.…”
Section: Effects Of Hypergravitymentioning
confidence: 42%
See 1 more Smart Citation
“…An over extended ankle at take off, but more flexed in the main part of the step cycle was also reported in adult suspended rats [28,42]. The ankle extension of suspended rats can be related to changes of paw pressure and muscles spindle stimulation [28,42]. This involves therefore a different mechanism than the one we observed on centrifuged mice.…”
Section: Effects Of Hypergravitymentioning
confidence: 42%
“…They were supposed to show an extensor bias because they constantly adopt a position with the hindlimb extended during their suspension. An over extended ankle at take off, but more flexed in the main part of the step cycle was also reported in adult suspended rats [28,42]. The ankle extension of suspended rats can be related to changes of paw pressure and muscles spindle stimulation [28,42].…”
Section: Effects Of Hypergravitymentioning
confidence: 67%
“…Indeed, after 14-day HU, we have previously demonstrated in the rat that Ia and II fiber discharges from the soleus during ramp-and-hold (3 and 4·mm) and sinusoidal stretches were increased because of changes in passive mechanical properties of the soleus during HU (De-Doncker et al, 2003). Consequently, the stretches could be better transmitted to the muscle spindles after a HU period and could be related to an increase in the connective tissue, as previously proposed by authors in tenotomized (Hnik and Lessler, 1973) and shortened immobilized muscles (Gioux and Petit, 1993;Maier et al, 1972;Tardieu et al, 1982).…”
Section: Recoverymentioning
confidence: 95%
“…Hnik et al (1977) reported quantitative changes in electroneurograms (ENGs) of the rat soleus nerve after the muscle had been de-efferented at birth. Changes in the spindle afferent discharges of cat muscles due to immobilization have been reported (Gioux and Petit, 1993;Nordstrom et al, 1995) and the Ia and II fibers of rat soleus muscle spindles were recently found to be more sensitive after a period of hypodynamia-hypokinesia (De-Doncker et al, 2003b). These changes in spindle afferent discharge may be due to changes in the spindle structure and/or to changes in the elastic properties of the muscle-tendon elements linked to the muscle spindles.…”
Section: Introductionmentioning
confidence: 93%